Aortic valve reconstruction with autologous pericardium in a patient with osteogenesis imperfecta. Issue 10 (5th October 2018) - Güllü, A Ümit; Senay, Sahin; Ozkan, Basak; Kocyigit, Muharrem; Alhan, Cem
Abstract: Cardiac valve surgery for patients with osteogenesis imperfecta is associated with a high incidence of complications such as perioperative bleeding and valve detachment. In this report, we present a patient who was diagnosed with osteogenesis imperfecta and severe aortic insufficiency and also discussed treatment options.